LIMIT OF DETECTION (LOD) AND LIMIT OF QUANTITATION (LOQ) OF DR 1900 SPECTROPHOTOMETER FOR DYES ANALYSIS - Wijayanti; Siti Rochmah (Politek ATK Yogyakarta Press, 2024)
Dyes is not easily degraded in the environment. It can be causing environmental pollution. The concentration of these dyes must be monitored when using it in a process. The most common method to measuring dye’s concentration is spectrometry, such as using dr 1900 spectrophotometer. There for, it necessary to know the limit of detection (lod) and limit of quantitation (loq) of the spectrophotometer. This study aims to determine the ability of the dr 1900 spectrophotometer to analyze ay-25 by determining the lod dan loq values. The results showed that the lod value was 0.01871 mg/l and the loq was 0.02308 mg/l. This means that dr 1900 spectrophotometer is capable pf providing a response for the analysis of ay-25 dye with a minimum analyte amount of 0.01871 mg/l, and if the measurement f ay-25 dye using the dr 1900 spectrophotometer show a value of 0.02308 mg/l or higher, then the mausrement results are considered to have a good accuracy and precision.